Acute stress-induced antinociception is cGMP-dependent but heme oxygenase-independent - Carvalho-Costa,P.G. (2014)
Endogenous carbon monoxide (CO), which is produced by the enzyme heme oxygenase (HO), participates as a neuromodulator in physiological processes such as thermoregulation and nociception by stimulating the formation of 3′,5′-cyclic guanosine monophosphate (cGMP). In particular, the acute physical restraint-induced fever of rats can be blocked by inhibiting the enzyme HO. A previous study reported that the HO-CO-cGMP pathway plays a key phasic antinociceptive role in modulating noninflammatory acute pain. Thus, this study evaluated the involvement of the HO-CO-cGMP pathway in antinociception induced by acute stress in male Wistar rats (250-300 g; n=8/group) using the analgesia index (AI) in the tail flick test. The results showed that antinociception induced by acute stress was not dependent on the HO-CO-cGMP pathway, as neither treatment with the HO inhibitor ZnDBPG nor heme-lysinate altered the AI. However, antinociception was dependent on cGMP activity because pretreatment with the guanylate cyclase inhibitor 1H-[1,2,4] oxadiazolo [4,3-a] quinoxaline-1-one (ODQ) blocked the increase in the AI induced by acute stress.